2011
DOI: 10.1088/1674-1056/20/8/088701
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lane change on stability analysis for two-lane traffic flow

Abstract: This paper deals mainly with the influence of lane changing behaviours on the stability of two-lane traffic flow under a periodic boundary condition. Following the description of an optimal velocity model for two vehicle groups and the derivation of their stability conditions, the feedback signals, which involve information about vehicles from both lanes acting on the two-lane traffic system, are introduced into the optimal velocity model. The control signals play a role in alleviating the traffic jam only if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 35 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…As can be seen from Table 3 that the drivers and road traffic environment were the main factors causing frequent lane‐changing behaviour, among which the drivers were the main factor. By comparing some scholars’ research [34] on the factors that affect drivers’ lane‐changing behaviour from the four aspects: people, vehicles, roads and environment, it can be concluded that the results obtained in this paper are similar to those in previous studies, which further proves that the research results in this paper are reliable.…”
Section: Resultssupporting
confidence: 82%
“…As can be seen from Table 3 that the drivers and road traffic environment were the main factors causing frequent lane‐changing behaviour, among which the drivers were the main factor. By comparing some scholars’ research [34] on the factors that affect drivers’ lane‐changing behaviour from the four aspects: people, vehicles, roads and environment, it can be concluded that the results obtained in this paper are similar to those in previous studies, which further proves that the research results in this paper are reliable.…”
Section: Resultssupporting
confidence: 82%
“…As can be seen from Table 2 overtaking slower vehicles and the road traffic environment were the main factors causing frequent lane-changing on highway behavior, among which the drivers were the main cause factor. By comparing some scholars' research [12] on the factors that affect drivers' lane-changing behavior on highways from the four aspects: people, vehicles, roads, and traffic environment, it can be concluded that the results obtained in this paper are similar to those in previous studies, which further proves that the research results in this paper are reliable.…”
Section: B Traffic Flow Densitysupporting
confidence: 80%
“…Based on this, under the precondition of the existence of lateral friction and considering the interaction mechanism between vehicles on the two‐lane, Liang et al 42 proposed a two‐lane optimal speed model with lateral friction. And in this model, the dynamic equations of the vehicle ni$$ {n}_i $$ in the lane i$$ i $$ can be described as: {dyi,ni(t)false/italicdtgoodbreak=vi,ni+1(t)goodbreak−vi,ni(t),dqi,ni(t)false/italicdtgoodbreak=vi,nif(t)goodbreak−vi,ni(t),dvi,ni(t)false/italicdtgoodbreak=ai[]Vi()Yi,ni(t)goodbreak−vi,ni(t),nigoodbreak=1,2,,Ni,$$ \left\{\begin{array}{l}{dy}_{i,{n}_i}(t)/ dt={v}_{i,{n}_i+1}(t)-{v}_{i,{n}_i}(t),\\ {}\hfill \kern-3.6em {dq}_{i,{n}_i}(t)/ dt={v}_{i,{n}_i}^f(t)-{v}_{i,{n}_i}(t),\\ {}{dv}_{i,{n}_i}(t)/ dt={a}_i\left[{V}_i\left({Y}_{i,{n}_i}(t)\right)-{v}_{i,{n}_i}(t)\right],\end{array}\right.…”
Section: Two‐lane Car‐following Model With Lateral Friction and Preli...mentioning
confidence: 99%
“…In Reference 42, a two‐lane car‐following model with lateral friction is proposed and the stability conditions of the traffic flow of the model are given by using the H$$ {H}_{\infty } $$ norm method. In addition, based on the two‐lane car‐following model with lateral friction, the relative velocity information without time delay and the head‐spacing information with time delay are loaded respectively, and the stability conditions of traffic flow based on the improved model are obtained.…”
Section: Two‐lane Car‐following Model With Lateral Friction and Preli...mentioning
confidence: 99%